Vacuum-assisted biopsy is a viable alternative to surgical biopsy in the investigation of breast lesions of uncertain malignant potential. Issue 2 (April 2017) - Pieri, Andrew; Hemming, Diane; Westgarth, Jackie; Lunt, Linsley
Abstract: Aims: In patients presenting with a breast lesion, when initial core biopsy histology falls into the category of "uncertain malignant potential" (i.e. a B3 lesion), the next line of investigation has traditionally been a surgical biopsy (SBx). Vacuum-assisted biopsy (VAB) may be a viable minimally invasive alternative to SBx for B3 lesions. The primary aims of this study were to establish whether VAB reduces the need for surgical biopsy and determine VAB sensitivity for carcinoma following initial B3 histology. Materials and methods: B3 lesion data was collected from 2004 to 2013 retrospectively, from a single institution that utilises both VAB and SBx. Results: A total of 413 lesions were categorised B3 on initial biopsy. Mean age was 61 years (range: 24–91 years). Mean follow up was 52 months (range: 19–60 months). 156 patients (38%) underwent VAB. Only 20% of patients underwent VAB in 2004, with an increase to 95% by 2013. VAB histology revealed twelve carcinomas, all of which progressed to surgical excision. In six cases, a SBx was required following VAB in order to provide further diagnostic information. In one case, carcinoma was missed on VAB. Conclusion: The increase in VAB use over time suggests that the procedure is well tolerated. The results demonstrate a VAB sensitivity of 92% for carcinoma diagnosis. In 96% of cases (150 of 156), VAB results were conclusive enough to avoid a subsequent SBx. This data suggests that VAB may be a preferable alternative to surgical biopsy for many B3 lesions.